Cambrian ( 510 Ma) ophiolites of the East Kunlun orogen, China: A case study from the Acite ophiolitic tectonic mélange. Issue 16 (10th December 2018) - Li, Ruibao; Pei, XianZhi; Li, Zuochen; Pei, Lei; Chen, Guochao; Wei, Bo; Chen, Youxin; Liu, Chengjun; Wang, Meng
ABSTRACT: The Acite ophiolitic mélange represents a remnant of the Proto-Tethys forearc oceanic lithosphere. Two gabbros yield zircon 206 Pb/ 238 U ages of 510-512 Ma. The magmatic rocks are divided into three subtypes: (1) Mid-ocean ridge basalt (MORB) -like forearc basalts (FABs), (2) Low-titanium tholeiitic gabbros (LTGs), and (3) Normal calc-alkaline dacites (CADs). The FABs have comparatively higher TiO2 concentrations (1.13–1.42 wt%) and show almost flat REE patterns. In the NMORB normalized trace element patterns, the FABs display flat distributions of high field strength element (HFSE). The ε Nd (t) values of FABs range from +4.0 to +4.8. These features are similar to the composition of Izu-Bonin-Mariana forearc basalts (FABs). LTGs are characterized by higher contents of MgO (8.85–9.95 wt%) and lower concentration of TiO2 (0.29–0.50 wt%). They show LREE-depleted patterns, however having comparatively lower total REE contents than those of FABs. The ε Nd (t) values of LTGs range from +7.4 to +8.4. These features show that LTG magmas originated from a progressively depleted mantle source. In contrast, the CADs having higher SiO2 contents (63.58–70.92 wt%) have higher total REE contents. In the NMORB normalized trace element patterns, CADs are characterized by enrichment of LILEs and depletion of HFSEs. CADs have negative ε Nd (t) values ranging from -9.8 to -10.5, which are likely suggestive of a crust-derived source. The rock association of FABs and LTGs, together with tectonic discrimination plots and regional data, suggest a forearc setting above the SSZ for Acite ophiolitic mélange. Graphical Abstract: